COMPARING THE EFFECT OF CONVENTIONAL PHYSIOTHERAPY AND RADIAL SHOCKWAVE THERAPY IN PATIENTS WITH CAPSULITIS ADHESIVE ON SHOULDER JOINT - Madzharova , R.; Simeonov , E. (EurasianUnionScientists, 2020)
Purpose: Capsulitis adhesive is a degenerative disease of soft tissues around the shoulder joint. Characterized by pain and limited movements in the shoulder joint. It has always been considered important because of the impact on the quality-of-life and long period of illness. Therefore, the use of noninvasive and safe techniques that can speed up the healing process of the disease is important.The aim of the follow-up the effect on pain and range of motion (ROM) after conventional physiotherapy versus radial shockwave therapy (RSWT) in the same patients with Capsulitis adhesive.Method: 10 patients ware treated for 2 months with a conventional physiotherapy without improvement and followed 6 weeks treatment with RSWT. Visual analogy scale (VAS) used for pain assessment, goniometry for the ROM and Neer test, Upper limb Activity of daily living (ADL) to objectitize the patient state before and after both therapies.Results: The patient's condition has not improved after conventional therapy. The treatment with RSWT provides a significant reduction of pain, increase ROM in the shoulder joint and improve ADL for the upper limb.Conclusions: Usage of RSWT alone is much better option compared to the conventional physiotherapy in patients with Capsulitis adhesive.